HUBUNGAN TUGAS KESEHATAN KELUARGA DENGAN TINGKAT DEMENSIA PADA LANSIA - Alvin Abdillah; Luluk Fauziyah J (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2020)
Background: Dementia in the elderly is a chronic confucius condition and the loss of cognitive abilities globally and progressively is associated with physical problems. Family health tasks as a support system are very important for people with dementia in order to do their daily activities. Purpose: This research aims to find out the relationship between family health tasks and dementia rates in the elderly. Methods: This research used analytical research type with cross sectional approach. Sample as much as 40 dementia elderly with total sampling technik. The dependent variable in this study was the dementia level in the elderly, while the independent variable was the family health task. Results: Based on the results of research, it was found that most of them have less family health duties and almost half of them with the level of dementia was severe. The Spearman Rank test resulted obtained p = 0.000 (?= 0.05), there was relationship between family health duties and the level of dementia in the elderly. Conclusion: Efforts made need to provide comprehensive and effective counseling from all sectors to the community to provide correct information about the importance of family duties or family roles to family members who have health problems, so that the community can pay attention to and care for sick families.Keywords: Family health tasks; Dementia; Elderly